2019
DOI: 10.1007/s13593-019-0604-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased grazing intensity in pastures reduces the abundance and richness of ground spiders in an integrated crop-livestock system

Abstract: Ground spiders can reflect the impacts of land-use intensification. In an integrated annual crop-livestock system, the grazing intensification can negatively influence the abundance and richness of ground spiders. We evaluated the difference in abundance, family and species richness, and species composition of ground spiders in the soybean and pasture environments, and the effect of grazing intensity on the spider community under a soybean-pasture rotation. We hypothesized that pastures would have higher spide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…These relationships were mediated by the drastic reduction of the grassland complexity and biomass promoted by higher grazing pressures (e.g., Malumbres-Olarte et al, 2013;Ferreira et al, 2020), which resulted in scarce sheltering and foraging options for spiders, as well as increased exposure to stressful conditions such as desiccation. These negative effects of grazing intensity on spider diversity have been already recorded for other grassland communities (Bell et al, 2001;Freiberg et al, 2020). Under high grazing pressure, ungrazed tall-layer plants probably played the role of secure 'islands', protected from cattle disturbance, with space availability (Schmitz & Suttle, 2001), support for webs (Wright & Coyle, 2000), access to water and food resources, and amelioration of abiotic conditions (de Keer et al, 1989), allowing for the coexistence of more spider species.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These relationships were mediated by the drastic reduction of the grassland complexity and biomass promoted by higher grazing pressures (e.g., Malumbres-Olarte et al, 2013;Ferreira et al, 2020), which resulted in scarce sheltering and foraging options for spiders, as well as increased exposure to stressful conditions such as desiccation. These negative effects of grazing intensity on spider diversity have been already recorded for other grassland communities (Bell et al, 2001;Freiberg et al, 2020). Under high grazing pressure, ungrazed tall-layer plants probably played the role of secure 'islands', protected from cattle disturbance, with space availability (Schmitz & Suttle, 2001), support for webs (Wright & Coyle, 2000), access to water and food resources, and amelioration of abiotic conditions (de Keer et al, 1989), allowing for the coexistence of more spider species.…”
Section: Discussionmentioning
confidence: 73%
“…The increase in grazing intensity usually favours the dominance of a short layer of prostrated grasses and forbs (Overbeck et al, 2007), while grazing alleviation or suppression favours tussock grasses and shrubs, developing a tall and homogeneous vertical structure (Quadros & Pillar, 1997). Wildlife responses to grazing in these ecosystems are largely taxa‐dependent (Ferreira et al, 2020), varying according to the organism's requirements regarding habitat openness and complexity (Luza et al, 2018; Andersen, 2019; Freiberg et al, 2020). Large herbivores can be very selective when browsing, which promotes grassland heterogeneity by generating a mosaic of grazed and ungrazed patches.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have made similar observations. Freiberg et al [70] mentioned Tetragnathidae species "exclusively" in ungrazed areas, in contrast with Lycosidae species that were abundant in grazed areas.…”
Section: The Effects Of Environmental Variables and The Role Of Forested Riparian Buffersmentioning
confidence: 99%
“…The predominance of the Araneae group in FA may be associated with the accumulation of leaves in the reference area, as this greater amount of leaves provides greater heterogeneity in the burlap microhabitat. Research by Freiberg et al (2020) showed that in an annual crop-livestock integration system, grazing intensification can negatively influence the abundance and richness of terrestrial spiders.…”
Section: Resultsmentioning
confidence: 99%